2019
DOI: 10.1016/j.ijid.2019.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute-stage chikungunya disease: Contribution of ultrasonographic joint examination

Abstract: Objective: Chikungunya (CHIKV) is an arbovirus that causes acute, debilitating polyarthritis. Its diagnosis can be difficult for clinicians not used to managing joint diseases or detecting synovitis. Joint Doppler ultrasonography (DUS) is a simple, non-invasive examination, able to visualize synovitis. Its diagnostic and prognostic value in rheumatoid arthritis is well-established. Methods: Patients with serologically proven acute arbovirosis where included. Clinical examination and joint count were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…No erosion was observed. Subcutaneous inflammatory infiltration (cellulitis) was observed in only a minor proportion of the participants [22]. In summary, RT-PCR was used in all studies that mentioned a diagnostic method, even in association with other alternative methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No erosion was observed. Subcutaneous inflammatory infiltration (cellulitis) was observed in only a minor proportion of the participants [22]. In summary, RT-PCR was used in all studies that mentioned a diagnostic method, even in association with other alternative methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Vijayalakshmi et al, 2017, showed that molecular mimicry between viral protein E1 and host proteins contributes to the development of arthritic manifestations by CHIKV through increased immune and inflammatory responses [21]. Another important study identified conserved regions of the alphavirus structural polyprotein that are homologous to human proteins involved in rheumatoid arthritis, which can be recognized by B cells and the MHC class II receptor [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the lack of high-strength evidence against CHIKF musculoskeletal manifestations, most recommendations have adopted therapies used for more common inflammatory arthropathies, with the use of chloroquine derivatives and disease modifying anti-rheumatic drugs (DMARDs). Such variety demonstrates the important gap on evidence on how to better manage CHIKV [12,13,14,15,16,17,18,19,20]. Biologic DMARD (bDMARD) have also been used to treat refractory cases of chronic arthritis [12,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Such variety demonstrates the important gap on evidence on how to better manage CHIKV [12,13,14,15,16,17,18,19,20]. Biologic DMARD (bDMARD) have also been used to treat refractory cases of chronic arthritis [12,17,19]. For patients with severe neuropathic pain, amitriptyline hydrochloride, gabapentin or pregabalin may be combined with the analgesics being used.…”
Section: Introductionmentioning
confidence: 99%